1989
DOI: 10.1093/oxfordjournals.aje.a115449
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of Deaths and Injuries Due to Tornadoes

Abstract: A case-control study, using both matched and unmatched controls, was carried out on individuals who were injured or killed by a series of tornadoes that passed through Ontario, Canada, on May 31, 1985. Many serious injuries (25%) and almost all (83%) deaths were the result of becoming airborne, while most minor injuries (94%) were due to being struck by objects. Head injury was the most common injury type. Few (21%) of those in buildings chose the recommended location, and most (61%) were not in the least dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 0 publications
2
43
1
2
Order By: Relevance
“…From the May 22, 2011, Joplin tornado, approximately 46 percent of the fatalities were aged 60 years or older, and further analysis revealed that approximately 38 percent of the fatalities were 65 years old or older. While some studies of U.S. tornadoes have found older populations (above 65 years of age) to be more vulnerable to casualty than other age groups (Moore 1958;CDC 1985;Sanderson 1989;Carter, Millson, and Allen 1989;Lillibridge 1997;Fernandez et al 2002), Fig. 4-18 shows that the two distributions are different and that older people made up more of the Joplin deaths than would be expected from the U.S. data.…”
Section: Age-deathsmentioning
confidence: 87%
“…From the May 22, 2011, Joplin tornado, approximately 46 percent of the fatalities were aged 60 years or older, and further analysis revealed that approximately 38 percent of the fatalities were 65 years old or older. While some studies of U.S. tornadoes have found older populations (above 65 years of age) to be more vulnerable to casualty than other age groups (Moore 1958;CDC 1985;Sanderson 1989;Carter, Millson, and Allen 1989;Lillibridge 1997;Fernandez et al 2002), Fig. 4-18 shows that the two distributions are different and that older people made up more of the Joplin deaths than would be expected from the U.S. data.…”
Section: Age-deathsmentioning
confidence: 87%
“…Oversykelighet og overdødelighet relatert til andre ekstreme vaersituasjoner der transport, elektrisitet og andre leveranser er mangelfulle, slik som etter en orkan eller et enormt snøfall er rapportert, men direkte årsaker og mekanismer er lite studert (10)(11)(12).…”
Section: English Summaryunclassified
“…Snøfall på mer enn 3 cm i Pennsylvania, USA, er vist å øke mortaliteten hos eldre, men også hos middelaldrende menn som følge av hjertesykdom, sykdommer i respirasjonsorganene og cerebrovaskulaer sykdom (12). Høy alder er vist å vaere en risiko for død som følge av tornadoer (11). I Norge har vi erfaringer fra orkanen som rammet Nord-Vestlandet første nyttårsdag 1992 og førte til store ødeleggelser og sviktende elektrisitetsforsyning i deler av Nordmøre i opptil fem døgn.…”
Section: Eldre Personer Er Sårbare I Ekstreme Vaersituasjonerunclassified
“…Carter et al surveyed tornado victims and found that only 21% of those in a building when a tornado hit chose the recommended safe location (42). As the Puerto Rico flood study revealed (30), educating people not to cross floodwaters by car or bike is a priority.…”
Section: Capacity To Adapt To Climate Changementioning
confidence: 99%